Autophagy Gene Panel-Based Prognostic Model in Myelodysplastic Syndrome - Wang, Ming-Jing; Liu, Wei-Yi; Wang, Xue-Ying; Li, Yu-Meng; Xiao, Hai-Yan; Quan, Ri-Cheng; Huang, Gang; Hu, Xiao-Mei (Frontiers in Oncology, 2021)
Abnormal autophagy is related to the pathogenesis and clinical symptoms of myelodysplastic syndrome (MDS). However, the effect of autophagy-related genes (ARGs) on the prognosis of MDS remains unclear. Here, we examined the expression profile of 108 patients with MDS from the GSE58831 dataset, and identified 22 genes that were significantly associated with overall survival. Among them, seven ARGs could be used to divide patients with MDS into high- and low-risk groups. The overall survival of patients with high-risk scores based on these seven ARGs was shorter than patients with low-risk scores in both the training cohort (hazard ratio [HR] = 1.322, 95% confidence interval [CI]: 1.158–1.51; P <0.001) and the validation cohort (HR = 1.05, 95% CI: 1–1.1; P <0.01). The area under the receiver operating characteristic curve (AUROC) was 0.856 and 0.769 after three years in the training cohort and validation cohort, respectively, and 0.87 and 0.821, respectively, after five years. Our data indicate these seven ARGs can predict prognosis in patients with MDS and could guide individualize treatment.